Aprendendo e ensinando o sistema de numeração decimal: uma contribuição à prática pedagógica do professor - Guimarães, Anilda Pereira da Silva (2006)
The central question of the present study is to identify the epistemological knowledge that the teachers-trainees possess regarding the characteristics (properties) of the decimal numbering system; its purpose is to offer a contribution to the pedagogic practice of the teachers who work within the Basic Literacy Cycle, in terms of what concerns both the acquisition of contents and the development of the knowledge that helps them in the elaboration of adequate strategies to working with the Decimal Numbering System in the classroom. The study is based on the constructivist sociointeractionist approach to teaching Mathematics and it constitutes, in itself, a methodological intervention with the teachers-trainees engaged in the Professional Qualification Program in Basic Education of the Federal University of Rio Grande do Norte. The foundations of the study were found in investigations of researchers who had carried out studies on the construction of numerical writing, showing, for instance, that the construction process of ideas and procedures involved in groupings and changes to base 10 take a lot longer to be accomplished than one can imagine. A set of activities was then elaborated which could not only contribute to the acquisition of contents but that could also make the teachers-trainees reflect upon their teaching practices in the classroom so that in this way they will be able to elaborate more consistent didactic approaches, taking into consideration the previous knowledge of the students and also some obstacles that often appear along the way. Even when teachers have access to the most appropriate dicactic resources, the lack of knowledge of the content and of the real meaning of that content make the Decimal Numbering System, a subject of fundamental importance, be taught most times in a mechanical way. The analisys of the discussions and behaviours of the teachers-trainees during the activities reavealed that they made them reflect upon their current practices in the classroom and that, as a whole, the aims of each of the activities carried out with the teachers-trainers were reached